ANALISIS YURIDIS PERJANJIAN JUAL BELI EMAS MELALUI MEDIA INTERNET ANTARA NASABAH DENGAN PT. PEGADAIAN (PERSERO) BERDASARKAN HUKUM PERDATA INDONESIA - , DWI MEIDY RIYANTO ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Gold trading activities via internet that is provided by PT. Pegadaian (Persero) in a facility called the e-Pegadaian Mulia Galeri 24 makes the process of buying gold electronically can happen automatically. The purpose of this study was to determine the suitability of a gold purchase agreement between the customer via the Internet with PT. Pegadaian (Persero) is reviewed by the Indonesian Civil and determine legal protection for the customers in buying and selling of gold through the internet with PT. Pegadaian (Persero) as well as the legal consequences to the parties associated with the Consumer Protection Law and the Law on Information and Electronic Transactions. Buying and selling over the internet is basically a modern model of purchase and sale transactions that apply technological innovations such as the Internet as a medium of transaction. General rules of engagement and purchase set out in Book III of the Civil Code applies as the legal basis for the activity of buying and selling over the internet in Indonesia. Problems that arise in trading activity over the internet is currently valid agreement, binding purchase agreement, the transfer of rights mechanism, the relationship of law and accountability of the parties involved, the legality of electronic records and document digital signatures as evidence, legal protection for the parties and the dispute resolution mechanism in the event of payment inaccuracies. Results and discussion of research that has been done can the authors note that the gold purchase agreement between the customer via the Internet with PT. Pegadaian (Persero) in accordance with the Civil Code, and in accordance with the lawful under Article 1320 of the Civil Code as well as regulated in Article 47 paragraph (2) of Government Regulation on the Implementation of Electronic Transaction System and the terms regulating the validity of electronic contracts. One form of protection against customers gold purchase agreement via the Internet with PT. Pegadaian (Persero) is a refund if there is a refund of excess payment in gold prices following other costs that are transferred by customers to the accounts of PT. Pegadaian (Persero) through the facilities of the ClickPay Bank Mandiri. Customers are entitled to claim back payment made when the PT. Pegadaian (Persero) exercise its right to cancel the transaction when the customer makes a payment that does not fit / less than the amount of the bill transactions. Dispute resolution through consultation and litigation in state court pathways authorized clients also can be reached by a gold purchase agreement via the Internet with PT. Pegadaian (Persero).